Accurate and Sensitive Determination Method for Procymidone and Chlorflurenol in Municipal Wastewater, Medical Wastewater and Irrigation Canal Water by GC-MS After Vortex Assisted Switchable Solvent Liquid Phase Microextraction - Kapukiran, Fatih; Firat, Merve; Chormey, Dotse Selali; Bakirdere, Sezgin; Ozdogan, Nizamettin (SPRINGER, 2019)
In this study, the detection power of a gas chromatography mass spectrometer (GC-MS) for procymidone and chlorflurenol was significantly enhanced using switchable solvent liquid phase microextraction (SS-LPME) as a preconcentration tool. This was achieved by a comprehensive optimization of significant parameters to the SS-LPME method such as switchable solvent amount, concentration and amount of sodium hydroxide, pH effect and mixing effect. The optimum experimental conditions obtained were used to determine analytical figures of merit for the analytes. The limits of detection obtained were 0.44 and 2.9ng/mL for procymidone and chlorflurenol, respectively. The optimum method was applied to water sampled from an irrigation canal and two wastewater samples. The samples were spiked at two concentrations and the percent recovery results obtained ranged between 86 and 115% for both analytes. The recovery results together with the low standard deviations recorded validated the method as accurate and precise.
Keywords: Pesticide; Switchable solvent; GC-MS; Procymidone; Chlorflurenol; PESTICIDES; EXPOSURE; CHROMATOGRAPHY; SEPARATION; SAMPLES; CANCER; Environmental Sciences & Ecology; Toxicology